A Virtual Assessment, Training and Evaluation of Clinical Laboratory Technologists Amidst Peak COVID-19 Pandemic – An Observational Study: Virtual Training of Clinical Laboratory Technologists - Ahmed, Sibtain; Abid, Muhammad Abbas; Jahan, Farhat; Ozben, Tomris (Journal of Medical Biochemistry, 2022)
Medical technologists are considered a neglected group when it comes to academic interventions. We developed and implemented an educational intervention and assessment for the technologists based on an online questionnaire as a pre-test consisting of questions related to knowledge (n=5), attitude (n=3), and practices (n=4) of daily internal quality control (QC) monitoring via google docs survey tool. This study served multiple purposes. It allowed to keep the technologists engaged during the peak of the COVID-19 pandemic, while also improving the knowledge, attitude and practices about the internal quality control using Bio-Rad Unity Real Time (URT) QC software. Subjects were graded based on the scores they received out of 100 (0-60=poor; 61-79=good; 80-100=excellent). Training materials i.e., a set of 5 videos every week via e-mail were circulated. A voice-over PowerPoint presentation was also shared for easy comprehension. This activity was repeated after one month. A post-test was administered to assess the improvement. The results of the study show significant improvement in the technologists’ performance after the intervention.